2015
DOI: 10.1159/000381454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs Differentially Expressed in Lung Carcinoid Subtypes and Progression

Abstract: Aim: To extensively explore microRNA expression profiles in lung carcinoids in correlation with clinical and pathological features. Methods: A PCR-based array was employed in the screening phase to analyze 752 microRNAs in a discovery set of 12 lung carcinoids, including 6 typical (3 with lymph node metastasis) and 6 atypical (3 with lymph node metastasis). The results were validated by means of real-time PCR in 37 carcinoids, including 22 typical (4 with lymph node metastasis) and 15 atypical (7 with lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…It has been shown that miR-409-3p inhibit cell migration and/or invasion in fibrosarcoma (Weng et al 2012), bladder cancer ) and gastric cancer (Zheng et al 2012) cells. In addition, miR-21 upregulation was correlated with metastatic disease (Lee et al 2014, Rapa et al 2015, which was also observed in PanNET (Roldo et al 2006). This miR was shown to deregulate PTEN (Meng et al 2007), involved in the mTOR pathway and ANP32A/SMARCA4 (Schramedei et al 2011), two proteins that are involved in chromatin remodelling.…”
Section: Pulmonary Carcinoidsmentioning
confidence: 87%
See 2 more Smart Citations
“…It has been shown that miR-409-3p inhibit cell migration and/or invasion in fibrosarcoma (Weng et al 2012), bladder cancer ) and gastric cancer (Zheng et al 2012) cells. In addition, miR-21 upregulation was correlated with metastatic disease (Lee et al 2014, Rapa et al 2015, which was also observed in PanNET (Roldo et al 2006). This miR was shown to deregulate PTEN (Meng et al 2007), involved in the mTOR pathway and ANP32A/SMARCA4 (Schramedei et al 2011), two proteins that are involved in chromatin remodelling.…”
Section: Pulmonary Carcinoidsmentioning
confidence: 87%
“…Different studies have examined miRNA expression in pulmonary carcinoids using different profiling platforms comparing normal lung tissue and tumour, carcinoids and high-grade NEC as well as localized and metastatic disease (Lee et al 2012, Deng et al 2014, Mairinger et al 2014, Rapa et al 2015. Although these studies are difficult to merge, some recurrent deregulated miRNAs in lung NET progression were identified, including miR-129-5p, miR-409-3p and miR-155.…”
Section: Pulmonary Carcinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were the averages of 13 protein-altering mutations per sample (128). Differential expression of miRNAs in typical vs atypical lung carcinoids has also been reported (130).…”
Section: Nets Of the Lungmentioning
confidence: 90%
“…All but one miRNA (miR-431-5p) were found to be upregulated in the carcinoid group as compared to high-grade neuroendocrine carcinomas. Moreover, when evaluating the association between the 11 selected miRNAs and clinical and carcinoid pathological characteristics, four miRNAs (miR-129-5p, miR-129*, miR-22 and miR-141) were found downregulated in high-stage tumors, four miRNAs (miR-129-5p, miR-409-3p, miR-409-5p and miR-431-5p) were found downregulated in cases with vascular invasion and three miRNAs (miR-409-3p, miR-409-5p and miR-431-5p) were found downregulated in tumors with lymph node metastases (Rapa et al 2015). Similarly, miRNA expression pattern in GEP NENs has been extensively investigated (Ruebel et al 2010, Matthaei et al 2012, Li et al 2013a, Dossing et al 2014, Miller et al 2016), but few studies evaluated a possible prognostic role of miRNAs in GEP NEN.…”
Section: :6mentioning
confidence: 95%